A crystallographic and DFT study on a NHC complex of niobium oxide trifluoride. Issue 18 (16th September 2016) - Bortoluzzi, Marco; Ferretti, Eleonora; Marchetti, Fabio; Pampaloni, Guido; Zacchini, Stefano
Abstract: The complex [NbOF3 (Ipr)]2, 1, was afforded in crystalline form by reaction of NbF5 with the bulky NHC ligand 1, 3-bis(2, 6-diisopropylphenyl)imidazol-2-ylidene (IPr) in toluene by slow contact with moisture air. The molecular structure of1 was ascertained by X-ray diffraction, providing the first example of a dinuclear NbOF3 derivative and also a rare case of niobium compound with a monodentate NHC. A DFT investigation has shown that the Nb–C bond consists of a weak NHC to Nb σ donation, reinforced by an electrostatic contribution presumably favored by the presence of the ancillary fluoride ligands. The computed enthalpy for the dissociation of one Ipr from1 is ca. 36 kcal mol −1 . The presence of bulky 2, 6-diisopropylphenyl substituents on the carbene ligand has negligible influence on the Nb–C bond, as highlighted by DFT analyses on simplified models. Abstract :